Health benefits of bluefin tuna consumption: (Thunnus thynnus) as a case study - Chamorro, F.; Cassani, L.; Garcia-Oliveira, P.; Barral-Martinez, M.; Jorge, A. O. S.; Pereira, A. G.; Otero, Paz; Fraga-Corral, M.; P. P. Oliveira, M. Beatriz; Prieto, M. A. (Frontiers in Nutrition, 2024)
Consumers are increasingly interested in food products with high nutritional value and health benefits. For instance, fish consumption is linked with diverse positive health benefits and the prevention of certain widespread disorders, such as obesity, metabolic syndrome, or cardiovascular diseases. These benefits have been attributed to its excellent nutritional value (large amounts of high-quality fatty acids, proteins, vitamins, and minerals) and bioactive compounds while being relatively low-caloric. Atlantic Bluefin tuna (Thunnus tynnus) is one of the most consumed species worldwide, motivated by its good nutritional and organoleptic characteristics. Recently, some organizations have proposed limitations on its consumption due to the presence of contaminants, mainly heavy metals such as mercury. However, several studies have reported that most specimens hold lower levels of contaminants than the established limits and that their richness in selenium effectively limits the contaminants' bioaccessibility in the human body. Considering this situation, this study aims to provide baseline data about the nutritional composition and the latest evidence regarding the beneficial effects of Atlantic Bluefin Tuna consumption. A review of the risk-benefit ratio was also conducted to evaluate the safety of its consumption, considering the current suggested limitations to this species' consumption.